1999
DOI: 10.1007/s100249900132
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Hepatic Short-Chain l-3-Hydroxyacyl-Coenzyme a Dehydrogenase Deficiency: Clinical, Biochemical, and Pathological Studies on Three Subjects with This Recently Identified Disorder of Mitochondrial β-Oxidation

Abstract: This report describes the clinical, biochemical, and pathological findings in three infants with hepatic short-chain L-3-hydroxyacyl-coenzyme A dehydrogenase (SCHAD) deficiency, a recently recognized disorder of the mitochondrial oxidation of straight-chain fatty acids. Candidate subjects were identified from an ongoing study of infant deaths. SCHAD analysis was performed on previously frozen liver and skeletal muscle on subjects with a characteristic urine organic acid profile. Autopsy findings were correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…differ both quantitatively and qualitatively from liver isoforms [56]. The alternative splicing machinery, which is tissue-specific and development-dependent [60,61], is probably responsible for differences between liver and skeletal muscle HADs.…”
Section: Had Is An Essential Enzyme For Catalyzing the Mitochondrial mentioning
confidence: 97%
See 2 more Smart Citations
“…differ both quantitatively and qualitatively from liver isoforms [56]. The alternative splicing machinery, which is tissue-specific and development-dependent [60,61], is probably responsible for differences between liver and skeletal muscle HADs.…”
Section: Had Is An Essential Enzyme For Catalyzing the Mitochondrial mentioning
confidence: 97%
“…However, a second isoform of HAD has now been cloned from skeletal muscle (GenBank accession number ). Moreover, it appears that skeletal muscle may contain HAD isoforms that differ both quantitatively and qualitatively from liver isoforms [56]. The alternative splicing machinery, which is tissue‐specific and development‐dependent [60,61], is probably responsible for differences between liver and skeletal muscle HADs.…”
Section: The Disease Referred To As Schad Deficiency Is Actually Due mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients 2 and 4 had normal levels of Type‐II protein, as judged by Western‐blot analysis, which was in line with their acyl‐CoA thioesterase activity. The same blot was stripped and re‐probed with an antibody generated to the mitochondrial short chain 3‐hydroxyacyl‐CoA dehydrogenase (SCHAD) [29], showing that this protein was unaffected in the patients. Quantification of the protein levels in patients relative to controls showed that patients 1 and 3 retained approximately 25–30% Type‐II protein; however, patient 5 retained only 10% of Type‐II protein.…”
Section: Resultsmentioning
confidence: 99%
“…Patients 2 and 4 had normal levels of Type-II protein, as judged by Western-blot analysis, which was in line with their acyl-CoA thioesterase activity. The same blot was stripped and re-probed with an antibody generated to the mitochondrial short chain 3-hydroxyacyl-CoA dehydrogenase (SCHAD) [29], showing that this protein was unaffected in the patients. Quantification of the protein levels Immunoprecipitation of acyl-CoA thioesterase activity was carried out by incubating human skin fibroblast homogenate with either preimmune serum or an affinity-purified antibody to rat cytosolic acyl-CoA thioesterase II (CTE-II).…”
Section: Western-blot Analysismentioning
confidence: 99%